Handling and propagation of Dendrobium ‘Iriana Jokowi’ in Bogor Botanic Gardens, Indonesia - EKA MARTHA DELLA RAHAYU (Smujo International, 2016)
Abstract. Rahayu EMD. 2016. Handling and propagation of Dendrobium ‘Iriana Jokowi’ in Bogor Botanic Gardens, Indonesia. Nusantara Bioscience 8: 258-263. Dendrobium ‘Iriana Jokowi’ is a new hybrid in Indonesia which has not been mass propagated yet. Mass propagation is necessary to ensure seedling availability. The orchid has been grown in the Orchids Greenhouse of Bogor Botanic Gardens since July 30, 2015. Handling and care for Dendrobium ‘Iriana Jokowi’, includes watering, provision of fertilizer, fungicides, and insecticides. Propagation has already been done is using seed culture. The seeds of Dendrobium ‘Iriana Jokowi’ were sown in four types of culture media, which are modified Vacin & Went (VW), modified Hyponex (HS), modified Knudson’s C (KC), and Knudson’s C (KCA). The seeds were able to germinate in all four tested media. The highest germination rate in the first 3 months after sowing (3 MAS) were found in KCA media, which are 93.21%. Germinated seed was then subcultured to four types of media in order to induce the growth of leaves and roots. The media used were T1A, T1V, HS, and KCA. After 5 months of planting (5 MAP), result showed that all four media were able to provide significant effect on the number of leaves and roots. The highest number of average leaves grown was 4.8 and found in T1A media. On the other hand, the highest number of average of roots grown was found in T1V media (4,2 roots).